The bridal suite - Alers, Rochelle (Alers, Rochelle. Innkeepers, 2019)
"With her besties in the Big Easy, Nydia Santiago is second-guessing staying behind in New York City. So when Jasmine Washington calls with the exciting news that she's getting married, Nydia happily rushes to New Orleans to be her maid of honor. Once she visits the lovely Garden District estate her friends are transforming into a luxury inn, she's wistful to join them in their venture. Then she meets the sexy engineer in charge of the renovation. With his seductive Southern drawl, Lamar Pierce could make her believe in love again . . . Lamar is confident, responsible, and settled--everything her ex, an aspiring Latin music singer, wasn't. But Lamar is also a widowed father to a pre-teen girl in need of a mother, something Nydia's not ready to be. When her ex makes a very public proposal, suddenly Nydia is running from the paparazzi--straight into Lamar's arms. But is she ready to take the leap from singlehood to wife and mother?. . ."--Provided by publisher.